Sơ bộ đánh giá hoạt tính sinh học từ một số loài san hô ở miền Bắc Việt Nam - Như Hằng, Trần Thị; Hương, Lê Mai; Hồng Hà, Trần Thị; Luyện, Nguyễn Đình; Chi, Hoàng Kim; Cường, Lê Hữu; Nghị, Đỗ Hữu; Giáp, Vũ Đình; Nhuân, Đỗ Thị; Phương Ly, Đặng Thị; et al. (Vietnam Journal of Chemistry, 2016)
Corals are marine invertebrates in the class Anthozoa of phylum Cnidaria. Among marine organisms, corals (soft and hard corals) are the producers of the value novel compounds. In this study, 24 organic extracts from soft corals and 28 organic extracts from hard corals were evaluated for their antimicrobial, cytotoxicity and antioxidant activities. The results showed that most of coral extracts (50/52) had antimicrobial activity against at least one test microorganism. 15 out of 52 CHCl3/MeOH extracts from the samples were cytotoxic to at least one of two cancer cell lines (Hepatocellular carcinoma, Hep-G2; and Human lung adenocarcinoma, LU-1), a higher proportion of cytotoxic extracts was recorded for extracts from soft corals to hard corals. None of the extracts exhibited free radical scavenging ability in 1,1-diphenyl-2-picrylhydrazyl (DPPH) based antioxidant assay. This preliminary result showed a potential for searching novel compounds. It will be a premise for elaborative investigation on biological data of phyla and species which show the national pharmaceutical potential and on conservation, exploitation in an effective and proper way. Keywords. Coral, bioactivity, antimicrobial, cytotoxic, antioxidant